Growth Analysis Based on Financial Ratios-Experience from Sugar Industry - Saković, Dušan; Jakšić, Dejan; Mijić, Kristina (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2020)
The paper analyzes the growth of the leading sugar companies in period 2016-2018. The research is based on the application of quantitative indicators of company growth (base and chain indices) based on data from the financial statements of the company from 2016-2018. Enterprise growth was measured on the basis of asset growth, capital growth, growth in sales revenue, net results and growth in the return on assets. Correlation analysis indicates that there is a positive, but not significant, relationship between growth indicators of sales revenue, equity and company assets. In 2018, there was a significant decline in sales revenue, while average growth indicators indicate a decrease in value of both assets and capital in 2016-2018.